2000
DOI: 10.1068/p2964
|View full text |Cite
|
Sign up to set email alerts
|

Raised Line Drawings are Spontaneously Explored with a Single Finger

Abstract: In this study we examine the strategies used by blindfolded subjects asked to freely explore raised line drawings and identify what is depicted in them. We were particularly interested in how often a single finger is spontaneously used because in several studies subjects are forced to use only one fingertip and the extent to which this restriction may depress haptic perception is unclear. The results suggest that despite a variety of strategies, people 'naturally' use single fingertips sufficiently often to al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 4 publications
2
36
0
Order By: Relevance
“…Our conclusion that searching with one Wnger is more eYcient than searching with more Wngers is largely in line with the results of Symmons and Richardson (2000). In their experiment participants could freely explore tactile line drawings.…”
Section: Discussionsupporting
confidence: 78%
“…Our conclusion that searching with one Wnger is more eYcient than searching with more Wngers is largely in line with the results of Symmons and Richardson (2000). In their experiment participants could freely explore tactile line drawings.…”
Section: Discussionsupporting
confidence: 78%
“…Some of the sighted subjects in the research reported here opted to feel both the targets and the choices with one hand. This is a normal strategy for sighted individuals (Symmons and Green 2000), but will slow haptic exploration. Sighted subjects often spontaneously explore tangible pictures with the index finger of one hand.…”
Section: Discussionmentioning
confidence: 99%
“…Collecting data from both one-and five-finger conditions, which was done in alternating order, allowed us to assess the performance of our algorithm for extracting index fingertip position in both one-and five-finger applications. Although using all five fingers may appear to be the most natural for haptic exploration, many participants in haptics studies will spontaneously use only their index finger (Symmons & Richardson, 2000).…”
Section: Data Collectionmentioning
confidence: 99%